Pb-free Radiation Shielding Glass Using Coal Fly Ash - Rachniyom, Watcharin; Tuscharoen, Suparat; Kaewkhao, Jakrapong; Pachana, Pumipat (Journal of Mathematical and Fundamental Sciences, 2015)
In this work, Pb-free shielding glass samples were prepared by the melt quenching technique using subbituminous fly ash (SFA) composed of xBi2O3 : (60-x)B2O3 : 10Na2O : 30SFA (where x = 10, 15, 20, 25, 30 and 35 by wt%). The samples were investigated for their physical and radiation shielding properties. The density and hardness were measured. The results showed that the density increased with the increase of Bi2O3 content. The highest value of hardness was observed for glass sample with 30 wt% of Bi2O3 concentration. The samples were investigated under 662 keV gamma ray and the results were compared with theoretical calculations. The values of the mass attenuation coefficient (Î¼m), the atomic cross section (Ïƒe) and the effective atomic number (Zeff) were found to increase with an increase of the Bi2O3 concentration and were in good agreement with the theoretical calculations. The best results for the half-value layer (HVL) were observed in the sample with 35 wt% of Bi2O3 concentration, better than the values of barite concrete. These results demonstrate the viability of using coal fly ash waste for radiation shielding glass without PbO in the glass matrices.